Pengaruh Saluran Komunikasi Interpersonal terhadap Keputusan Adopsi Inovasi Pertanian Bioindustri Integrasi Seraiwangi–Ternak di Provinsi Jawa Barat - nFN Rushendi; Sarwititi Sarwoprasdjo; Retno Sri Hartati Mulyandari (Jurnal Agro Ekonomi, 2016)
EnglishCitronella-livestock bio-industry farming system is an innovative integrated farming model consisting of citronella farming, livestock, and other farming and product processing related activities in a biomass and material circular manner. Development of this innovation is still going on, but innovation delivery to the local community is still sub-optimal. The reason is presumably due to some determinants of adoption decision including communication form, delivery method, innovation recipients, and technological innovation. The objective of the study is to analyze the level of adoption decision and the influence of interpersonal communication media. The study used survey method with descriptive quantitative approach using multinomial logistic regression. The location was selected purposively. The survey was conducted in the period of March–May 2016 from 230 farmers who were selected using cluster random sampling technique. Results indicated that technology components adopted by farmers including plant citronella, use of dung manure for organic fertilizer and household biogas, and yoghurt processing. Factors influencing innovation adoption decision are interpersonal communication media through talk, dialogue, and results show. Credibility factors of information sources influencing adoption decision are confidence level and competency of information sources from fellow farmers, existing institutions, extension workers, and staff of the experimental station.IndonesianPertanian bioindustri integrasi serai wangi-ternak merupakan model pertanian terpadu yang terdiri atas usaha tani serai wangi, peternakan, dan kegiatan usatani maupun pengolahan hasil lainnya dalam bentuk siklus biomassa dan materi. Pengembangan inovasi tersebut masih berjalan, namun penyampaian inovasi kepada masyarakat sekitar belum optimal. Hal ini disebabkan oleh beberapa faktor penentu keputusan adopsi termasuk bentuk komunikasi yang disampaikan, metode penyampaian, penerima inovasi, dan teknologi inovasi. Penelitian bertujuan untuk mengetahui tingkat keputusan adopsi dan pengaruh media komunikasi interpersonal. Penelitian menggunakan metode survei melalui pendekatan kuantitatif deskriptif dengan uji regresi multinomial logistic. Lokasi penelitian dipilih secara purposive di Desa Cikahuripan, Kecamatan Lembang, Kabupatan Bandung Barat. Penelitian dilakukan selama bulan Maret–Mei 2016 dengan jumlah responden sebanyak 230 petani yang dipilih dengan teknik cluster random sampling. Hasil penelitian menunjukkan bahwa komponen teknologi yang diadopsi petani meliputi menanam serai wangi, pemanfaatan limbah kotoran ternak menjadi pupuk organik dan biogas rumah tangga, serta membuat yoghurt. Faktor yang memengaruhi keputusan adopsi inovasi adalah media komunikasi interpersonal melalui ceramah, dialog, dan demonstrasi hasil. Faktor kredibilitas sumber informasi yang memengaruhi keputusan adopsi adalah tingkat kepercayaan dan kompetensi sumber informasi dari sesama petani, kelembagaan yang ada, penyuluh, dan staf Kebun Percobaan.